3/4*1/8++3/4*3/8-1/2*3/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(4\dfrac{3}{8}+5\dfrac{2}{3}=\dfrac{4\times8+3}{8}+\dfrac{5\times3+2}{3}\\ =\dfrac{35}{8}+\dfrac{17}{3}=\dfrac{35\times3+17\times8}{24}=\dfrac{241}{24}\\ ----\\ 2\dfrac{3}{8}+1\dfrac{1}{4}=\dfrac{2\times8+3}{8}+\dfrac{1\times4+1}{4}=\dfrac{19}{8}+\dfrac{5}{4}\\ =\dfrac{19+5\times2}{8}=\dfrac{29}{8}\\ ----\\ 2\dfrac{3}{8}-1\dfrac{1}{4}+5\dfrac{1}{3}=\left(2-1+5\right)+\left(\dfrac{3}{8}-\dfrac{1}{4}+\dfrac{1}{3}\right)\\ =6+\dfrac{3\times3-1\times6+1\times8}{24}\\ =6+\dfrac{11}{24}=6\dfrac{11}{24}\)
1)\(1\frac{3}{4}-1\frac{3}{8}:\left(\frac{3}{8}+\frac{9}{20}\right)=\frac{7}{4}-\frac{11}{8}:\frac{33}{40}=\frac{7}{4}-\frac{5}{3}=\frac{1}{12}\)
4 + 3 + 1 = 8; 8 - 4 - 2 = 2;
5 + 1 + 2 = 8; 8 - 6 + 3 = 5;
2 + 6 - 5 = 3; 8 + 0 - 5 = 3
7 - 3 + 4 = 8; 3 + 3 - 4 = 2
Lời giải chi tiết:
8 – 4 – 2 = 2 | 4 + 3 + 1 = 8 | 2 + 6 – 5 = 3 | 8 + 0 – 5 = 3 |
8 – 6 + 3 = 5 | 5 + 1 + 2 = 8 | 7 – 3 + 4 = 8 | 3 + 3 – 4 = 2 |
1*2*3*...*9-1*2*3*...*8-1*2*3*...8*8=9!-8!-8!*8
=8!*9-8!*1-8!*8
=8!*(9-1)-8!*8
=8!*8-8!*8
=0
\(4\dfrac{3}{8}+5\dfrac{2}{3}=\dfrac{35}{8}+\dfrac{17}{3}=\dfrac{241}{24}\)
\(2\dfrac{3}{8}+1\dfrac{1}{4}+3\dfrac{6}{7}=\dfrac{19}{8}+\dfrac{5}{4}+\dfrac{27}{7}=\dfrac{419}{56}\)
\(2\dfrac{3}{8}-1\dfrac{1}{4}+5\dfrac{1}{3}=\dfrac{19}{8}-\dfrac{5}{4}+\dfrac{16}{3}=\dfrac{155}{24}\)
2 = 1 + 1 6 = 2 + 4 8 = 5 + 3 10 = 8 + 2
3 = 1 + 2 6 = 3 + 3 8 = 4 + 4 10 = 7 + 3
4 = 3 + 1 7 = 1 + 6 9 = 8 + 1 10 = 6 + 4
4 = 2 + 2 7 = 5 + 2 9 = 6+ 3 10 = 5 + 5
5 = 4 + 1 7 = 4 + 3 9 = 7 + 2 10 = 10 + 0
5 = 3 + 2 8 = 7 + 1 9 = 5 + 4 10 = 0 + 10
6 = 5 + 1 8 = 6 + 2 10 = 9 + 1 1 = 1 + 0
Bài làm :
Ta có :
\(\frac{3}{4}\times\frac{1}{8}+\frac{3}{4}\times\frac{3}{8}-\frac{1}{2}\times\frac{3}{4}\)
\(=\frac{3}{4}\times\left(\frac{1}{8}+\frac{3}{8}-\frac{1}{2}\right)\)
\(=\frac{3}{4}\times0=0\)
Chúc bạn học tốt !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
=3/4* (1/8+3/8-1/2)
=3/4*(4/8-4/8)
=3/4 * 0
= 0